Maize grain zinc and iron concentrations as influenced by agronomic management and biophysical factors: a meta-analysis - Job Kihara; Sileshi, Gudeta W.; Bolo, Peter Omondi; Mutambu, Dominic Mwanzia; Sila, Andrew Musili (2023)
Human Zn and Fe deficiencies can be reduced through agronomic biofortification, but information on factors influencing maize grain-Zn and -Fe levels remains scant. This analysis: (1) Establishes the global distribution of Zn and Fe concentrations in maize grain; (2) Assesses different agronomic practices’ contributions to increasing maize-grain Zn and Fe levels; and (3) Identifies key biophysical factors to guide agronomic biofortification. Using 1,332 data points in 102 published papers from 24 countries, we estimated a 24% probability of grain-Zn concentrations exceeding the benchmark target of 38 mg kg−1.